Respuesta :

Answer: [tex]T=\frac{A-P}{PR}[/tex]

Step-by-step explanation:

Given the following formula provided in the exercise:

[tex]A=P+PRT[/tex]

You can follow the steps  shown below in order to solve for the variable [tex]T[/tex]:

 Step 1: You need to subtract [tex]P[/tex] from both sides of the equation. Then:

[tex]A-(P)=P+PRT-(P)\\\\A-P=PRT[/tex]

Step 2: Finally, you need to divide both sides of the equation by [tex]PR[/tex]. Then you get:

[tex]\frac{A-P}{PR}=\frac{PRT}{PR}\\\\T=\frac{A-P}{PR}[/tex]